2017
DOI: 10.1159/000478521
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thyroid Hormone on Urinary Concentrating Ability

Abstract: Background: Hypothyroidism has been associated with impaired urinary concentrating ability. However, previous reports on thyroid hormone and urinary concentrating ability in humans only studied a limited number of patients with autoimmune thyroid disease or used healthy controls instead of paired analysis within the same patients. Objective: To study the urinary concentrating ability in athyreotic patients with differentiated thyroid cancer on and off levothyroxine treatment as they are exposed to different th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…The results of the present study indicated that THW significantly increased serum Cr and decreased eGFR to an abnormal level, thus reflecting adverse effects on the kidney. These results are consistent with those of previous studies 8 , 9 , 12 , 13 , 17 . It is known that renal function is decreased in hypothyroidism owing to an increased serum Cr level 19 .…”
Section: Discussionsupporting
confidence: 94%
“…The results of the present study indicated that THW significantly increased serum Cr and decreased eGFR to an abnormal level, thus reflecting adverse effects on the kidney. These results are consistent with those of previous studies 8 , 9 , 12 , 13 , 17 . It is known that renal function is decreased in hypothyroidism owing to an increased serum Cr level 19 .…”
Section: Discussionsupporting
confidence: 94%
“…Complicating this issue of azotemia and hypothyroidism is that impaired urine concentrating ability has been reported in some, 26,27 but not all, 28 studies of human hypothyroid patients, an effect that can sometimes be reversed with thyroid hormone treatment. 26,27 When we compared our hypothyroid and euthyroid cats, however, cats destined to become hypothyroid were older, had higher pretreatment serum concentrations of creatinine, urea nitrogen, and SDMA, with a higher proportion having pretreatment USG <1.035 (57% vs 45%; Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…4,[19][20][21][22][23] Such azotemia would be expected to improve once thyroid hormone replacement therapy normalizes GFR and renal blood flow. [23][24][25] In addition, hypothyroidism has been reported to impair urine concentrating ability in some, 26,27 but not all, 28 studies of human patients, an effect that can sometimes be reversed with thyroid hormone treatment. 26,27 To our knowledge, no reports on urine concentration in hypothyroid cats, either with or without azotemia, exist.…”
Section: Introductionmentioning
confidence: 99%
“…The categories of thyroid dysfunction were classified based on the reference intervals for the hormones and pattern of derangement in the thyroid hormones profile. Euthyroid hyperthyroxinaemia: isolated elevation of FT 4 or TT 4 in the presence of TSH, FT 3 and TT 3 within reference limits [26].…”
Section: Definition and Classification Of Categories Of Thyroid Dysfunctionmentioning
confidence: 99%